Synthesis of Benzimidazole-Sulfonyl Derivatives and Their Biological Activities - Endale Mulugeta; Yoseph Samuel (Biochemistry Research International)
Currently, the synthesis of new compounds with potential bioactivities has become a central issue in the drug discovery arena. Among these new compounds, benzimidazole-sulfonyl scaffolds have vital applications in the fields of pharmaceuticals industries. Benzimidazole and sulfonyl compounds have remarkable biological activities, such as antibacterial, antifungal, anti-inflammatory, antiproliferative, carbonic anhydrase inhibitory, and α-amylase inhibitory activities. Furthermore, recent literature mentions the synthesis and bioactivities of some benzimidazole-sulfonyl hybrids. In this review, we focus on reviewing the synthesis of these hybrid scaffolds and their various types of biological activities of the compounds.